EVALUASI DAN PERBAIKAN DESAIN USER INTERFACE UNTUK MENINGKATKAN USER EXPERIENCE PADA APLIKASI MOBILE SIARAN TANGSEL MENGGUNAKAN METODE GOAL DIRECT DESIGN (GDD) - Diana Nur Yastin; Hendra Bayu Suseno; Viva Arifin (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2020)
Mobile Siaran is an official reporting application intended for the people of the city of Tangerang Selatan (South Tangerang). However, after conducting interviews with stakeholders and respondents, there were several problems with the display of the mobile application. From the results of the interview, it indicates that there are still some applications that need improvement. To fix the problem with the Mobile Siaran application display, the solution given is to improve the user interface design using the Goal Direct Design method. In addition, it also uses the success rate calculation technique and the System Usability Scale (SUS) to measure the usability value. Meanwhile, the User Experience Questionnaire (UEQ) measures the value of user experience. The result of this research is a user interface design made in stages in the Goal Direct Design method, namely research, modeling, requirements, frameworks, and refinement. The final evaluation, the results of the improvement using calculations, the success rate has increased from 93.5% to 99.3%, SUS from an average score of 58.19 which can be said to be quite satisfactory with the letter D value to 81.83 which can be accepted with the value of the letter A, while UEQ shows all aspects that have improved with very good and good criteria which means that improvements to user interface design can solve problems that exist in the application and improve the user experience.